Respon berbagai genotipe cabai rawit (Capsicum Frustescens L.) terhadap pemberian naungan insect net - Muhammad Rizki Al Amin; Setyono Setyono; Sulassih Sulassih (Universitas Djuanda, 2025)
Chili Papper (Capsicum frutescens L.) is a high-value horticultural commodity that is susceptible to excessive light intensity and pest attacks, particularly in cultivation systems under tree canopies. This study aims to characterize 10 genotypes of chili Papper (Capsicum frutescens L.) under shaded conditions using insect nets to evaluate the plants' morphological responses and productivity under low light intensity. The research was conducted at the Cibeureum Experimental Garden, Bogor, from February to September 2024, using a split-plot randomized complete block design (RCBD), with genotype (Bonita, Feira, Inul, Pulaipila Hijau, RF13, RF17, RF18, RF28, RF32, RF39) as the main plot and shading treatment (shaded and unshaded) as the subplot. Observed parameters included both quantitative and qualitative traits. The analysis revealed that the interaction between genotype and shading had a significant effect on fruit length, pedicel length, and pedicel diameter. The Feira genotype showed a positive response to shading, particularly in terms of fruit and pedicel length. The Inul genotype exhibited the best in terms of fruit diameter and fruit weight per plant and is recommended for cultivation under tree canopies. Shading generally reduced the number and weight of fruits per plant. Qualitative traits such as plant habit, anther coloration, and flower position were not significantly affected by shading. This study highlights the importance of selecting genotypes that are adaptive to low light intensity for use in cultivation under canopy.